Екологічний стан компонентів довкілля природно заповідного фонду Харківської області (на прикладі заказників «Рязанова балка», «Кочетоцький», «Цикалове») - Гололобова, Олена Олександрівна; Gololobova, Olena (Харкiв : Харкiвський нацiональний унiверситет iмені В. Н. Каразiна, 2012)
Розглянуті особливості поліелементного забруднення важкими металами охороняємих територій Харківської області на прикладі заказників «Рязанова балка», «Кочетоцький», «Цикалове». Показано, що в умовах помірного антропогенного навантаження хімічний склад рослин детермінується механізмами генетичного контролю рослин. Система «коріння – кора» дерев’янистих рослин є ефективним індикатором стану довкілля.

The features of polyelemental contamination by the heavy metals of secured territories of the Kharkiv area on the example of wildlife preserves of «Ryazanova balka», «Kochetoksky», «Tsikalove» are considered. It is shown that in the conditions of the moderate anthropogenic loading the chemical composition of plants is determined by the mechanisms of genetic control of plants. The system "a root - a bark" of woody plants is the effective indicator of the state of environment.
Ecological state of environmental components of natural reserve fund of the Kharkiv region (for example, nature reserves «Ryazanov balka», «Kochetoksky», «Tsikalove»)
Keywords: заказник; забруднення; коефіцієнт концентрацій; важкі метали; генетичний контроль; компоненти довкілля; заказник; загрязнение; коэффициенты концентраций; тяжелые металлы; генетический контроль; компоненты окружающей среды; wildlife preserve; contamination; coefficients of concentrations; heavy metals; genetic control; components of environment; NATURAL SCIENCES::Biology::Terrestrial, freshwater and marine ecology::Terrestrial ecology